Millennial length summer sunshine reconstructions from stable carbon isotope ratios in tree rings from across Fennoscandia. - Gagen, M.; McCarroll, D.; Zorita, E.; Young, G.; Jalkanen, R.; Loader, N.; Robertson, I.; Grudd, H.; Kirchhefer, A.
1